JURIDICAL REVIEW RESOLUTION OF TORT DISPUTES IN ARISAN ACTIVITIES - Khoirala, Rossyita; mahanani, Anajeng Esri Edhi (JARES (Journal of Academic Research and Sciences), 2024)
Gathering activities are often carried out by the surrounding community which are unknowingly recognized as a form of agreement. Such as the gathering activity in Margomulyo Village, Tuban Regency, where the practice of the gathering agreement is carried out verbally based on a mutual agreement which gives birth to rights and obligations to be fulfilled. Wanprestasi, namely when the rights and obligations are not fulfilled properly which results in losses for other parties. This research method, namely empirical law, is the law of reviewing or looking at itself from outside elements (law) based on social phenomena in the real world (empirical) that influence legal behavior both personally and institutionally in society and institutions. law. The approach used in this study is a qualitative approach. Legal materials in research are primary legal materials, secondary legal materials, and tertiary legal materials. The results of the study can be concluded that the arisan agreement is verbalhas the legal force to bind the parties who make it, so that if a default occurs it can be used as a basis for declaring someone to have committed a wanprestasi. Meanwhile, settlement of default disputes can be resolved either through litigation or non-litigation.